2021
DOI: 10.1371/journal.pone.0244141
|View full text |Cite
|
Sign up to set email alerts
|

Are the classic false belief tasks cursed? Young children are just as likely as older children to pass a false belief task when they are not required to overcome the curse of knowledge

Abstract: The question of when children understand that others have minds that can represent or misrepresent reality (i.e., possess a ‘Theory of Mind’) is hotly debated. This understanding plays a fundamental role in social interaction (e.g., interpreting human behavior, communicating, empathizing). Most research on this topic has relied on false belief tasks such as the ‘Sally-Anne Task’, because researchers have argued that it is the strongest litmus test examining one’s understanding that the mind can misrepresent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(4 citation statements)
references
References 98 publications
1
3
0
Order By: Relevance
“…Also, hindsight bias was greater in older adults than in 10to 17-year-olds. This U-shaped data pattern conceptually replicates prior work that used a smaller age range with smaller samples, often using general-knowledge tasks focusing on childhood or adulthood (e.g., Bayen et al, 2006;Bernstein, Erdfelder, et al, 2011;Ghrear et al, 2020Ghrear et al, , 2021Groß & Pachur, 2019;Pohl et al, 2010Pohl et al, , 2018. False-belief reasoning errors were significant in all age groups but did not differ with age.…”
Section: Discussionsupporting
confidence: 80%
“…Also, hindsight bias was greater in older adults than in 10to 17-year-olds. This U-shaped data pattern conceptually replicates prior work that used a smaller age range with smaller samples, often using general-knowledge tasks focusing on childhood or adulthood (e.g., Bayen et al, 2006;Bernstein, Erdfelder, et al, 2011;Ghrear et al, 2020Ghrear et al, , 2021Groß & Pachur, 2019;Pohl et al, 2010Pohl et al, , 2018. False-belief reasoning errors were significant in all age groups but did not differ with age.…”
Section: Discussionsupporting
confidence: 80%
“…Across hundreds of experimental replications, 3-yearolds consistently fail, and it is not until around 4 or 5 years of age that children pass this task [3,16,19,20; see 21 for a meta-analysis]. However, several researchers have challenged the validity of the standard false belief tasks [22], proposed alternative explanations for the age-related changes observed between 3 and 5 years of age [23], and demonstrated that much younger children, perhaps even infants, can reason about false beliefs if the tasks are made easier by removing extraneous task demands [24].…”
Section: Background: Defining and Measuring 'Tom'mentioning
confidence: 99%
“…Another major limitation with the bulk of the previous literature relying on standard false belief tasks is that these measures unnecessarily involve overcoming a fundamental cognitive bias known as the 'curse of knowledge' bias, the tendency to be biased by one's own knowledge when reasoning about a more naive perspective [33,45]. As such, the individual differences in children's performance on this task may reflect more general cognitive abilities rather than, or in addition to, differences in ToM (for recent evidence [23,46], see also [6,47]).…”
Section: Background: Defining and Measuring 'Tom'mentioning
confidence: 99%
“…Two significant challenges were also identified [ 63 ]: different tests meant to measure distinct constructs actually track the same ToM construct (heterogeneity), while a single test meant to be measuring one construct can track multiple social cognitive abilities (lack of specificity). For example, the SAT is an elicited-response task demanding executive functions [ 29 , 73 ], while it has been also established that the performance of children on this dyadic assessment depends on factors beyond false-belief understanding, as children closely monitor the conduct of their assessor and react to it, thereby employing other social cognitive skills to complete the task successfully [ 40 ]. Furthermore, the explicit attribution of false beliefs is closely related to language [ 19 , 62 ], among other factors affecting individual differences in ToM [ 37 ].…”
Section: Theory Of Mind and Social Cognitive Abilitiesmentioning
confidence: 99%